2000
DOI: 10.1136/jcp.53.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of gastric mucosa associated lymphoid tissue (MALT) lymphomas: high grade transformation and comparison with diffuse large B cell lymphomas without MALT lymphoma features

Abstract: Aims-To investigate the clinicopathological diVerences among gastric low grade MALT lymphomas (low MALT), large B cell lymphomas with low grade components (secondary high grade MALT lymphomas, high MALT), and diVuse large B cell lymphomas without low grade features (primary high grade MALT lymphomas, DLL). Methods-Clinicopathological and morphological characters of 126 gastric lymphoma cases were studied: 82 cases of low MALT lymphoma including 40 that were surgically resected, 17 cases of high MALT lymphoma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 17 publications
3
15
1
2
Order By: Relevance
“…Regression results suggest that more steps are required for the development of marginal zone B‐cell lymphoma ( m = 5.7) than for the carcinogenesis of diffuse large B‐cell lymphoma ( m = 4.2). This interpretation of our results supports the hypothesis that MZBL and DLBL may have different lines of development as suggested by the findings of Yoshino et al 23. in contrast to the hypothesis that MZBL precedes DLBL 10.…”
Section: Discussionsupporting
confidence: 93%
“…Regression results suggest that more steps are required for the development of marginal zone B‐cell lymphoma ( m = 5.7) than for the carcinogenesis of diffuse large B‐cell lymphoma ( m = 4.2). This interpretation of our results supports the hypothesis that MZBL and DLBL may have different lines of development as suggested by the findings of Yoshino et al 23. in contrast to the hypothesis that MZBL precedes DLBL 10.…”
Section: Discussionsupporting
confidence: 93%
“…Although several previous studies reported that PGLs affect men more often than women, this seems because they included symptomatic patients who visited the hospital, and consequently in those studies, DLBCL and MALT lymphoma were common types of PGL like the outpatient group of our study. This is compatible with previous report from Japan where gastric MALT lymphoma showed female predominance, while high‐grade gastric lymphoma showed male predominance . Second, gastric adenocarcinoma developed less frequently in middle‐aged women than middle‐aged men or elderly people.…”
Section: Discussionsupporting
confidence: 92%
“…Cabras et al [16] advocated multiple pathways to high grade transformation. The time taken for high grade transformation was estimated at about 10 years by Yoshino et al [17] , which was not definite with our study. On the other hand, there were 4 cases in our study who had been diagnosed as low grade MALT lymphoma by preoperative gastroscopy, and they were diagnosed as higher grade lymphoma after H pylori eradication or surgery.…”
Section: Discussioncontrasting
confidence: 48%